2020
DOI: 10.1016/j.jsxm.2020.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Climacturia and Associated Patient/Partner Bother in Patients with History of Definitive Therapy for Prostate Cancer

Abstract: Background Climacturia is an under-reported complication of definitive therapy for prostate cancer (PCa) - that is, radical prostatectomy (RP) and/or radiation therapy (RT). Aim We sought to identify the prevalence and predictors of climacturia and associated patient/partner bother in patients with and without prior PCa treatment. Methods We analyzed a databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…Patient perception of partner bother is consistently noted to be a major source of distress among those experiencing climacturia. Salter and colleagues found this metric to have the greatest odds of predicting patient bother on multivariate analysis [8,16,19]. Furthermore, two studies examining both heterosexual and homosexual men found shorter relationship duration was associated with increased patient bother due to climacturia [16,22].…”
Section: Prevalence and Clinical Significancementioning
confidence: 99%
See 3 more Smart Citations
“…Patient perception of partner bother is consistently noted to be a major source of distress among those experiencing climacturia. Salter and colleagues found this metric to have the greatest odds of predicting patient bother on multivariate analysis [8,16,19]. Furthermore, two studies examining both heterosexual and homosexual men found shorter relationship duration was associated with increased patient bother due to climacturia [16,22].…”
Section: Prevalence and Clinical Significancementioning
confidence: 99%
“…Climacturia can cause significant negative psychosexual effects, with approximately half of patients reporting some level of bother due to the symptoms. Affected patients report lower sexual satisfaction, as well as higher rates of depression and anxiety [6,10,12,16,19]. In comparison, a 3year follow-up of the landmark CEASAR trial found stress urinary incontinence (SUI) to cause bother in only 19% of affected men, despite this symptom being a more recognized and counseled effect of RP [20,21].…”
Section: Prevalence and Clinical Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Climacturia is a bothersome condition in which patients report incontinence with orgasm. While previously underreported, it is now thought to be prevalent in 23% to 40% of men post radical prostatectomy (83,84). A retrospective review by Nolan et al found that in men with general stress incontinence plus climacturia, AdVance slings improved both subjective frequency of climacturia as well as associated bother (85).…”
Section: Sling For Climacturiamentioning
confidence: 99%